Preparation method of WC reinforced composite coating
By using the laser cladding method of ZrO2-WC composite powder and nickel-based alloy powder, the problems of decarbonization, burning and uneven distribution of WC during laser cladding are solved, and the preparation of high-performance WC enhanced composite coating is achieved.
Patent Information
- Application Number
- CN202510021622.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-07
AI Technical Summary
During the laser cladding WC-enhanced composite coating, WC is prone to decarbonization and burning, and the high density leads to uneven distribution in the coating, forming stress concentration and inducing cracks.
ZrO2-WC composite powder was used as the reinforced phase, mixed with the nickel-based alloy powder in a certain proportion, and the composite coating was prepared by laser cladding. The ZrO2-WC composite powder is formed through a core-shell structure, and the volume ratio of low-density ZrO2 and high-density WC is regulated, so that the density of the composite powder is similar to that of the parent powder, avoiding the decarbonization, burning and uneven distribution of WC.
The decarbonization, burning and uneven distribution problems of WC are effectively avoided, and a high-performance WC-enhanced composite coating with uniform phase distribution and crack-free composite coating is obtained.
Smart Images

Figure CN119824408A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a laser cladding coating, in particular to a method for preparing a WC reinforced composite laser cladding coating. Background Art
[0002] Tungsten carbide (WC) has a high melting point, high hardness and low thermal expansion coefficient, and has good wettability with nickel-based alloys. It is a commonly used ceramic reinforcement phase material for nickel-based alloys. Adding WC ceramic particles to nickel-based alloy powders to reinforce the metal-based ceramic composite coating through laser cladding can organically combine the toughness and good processability of metals with the excellent wear resistance, corrosion resistance, high temperature resistance and oxidation resistance of ceramic materials, and has potential application prospects.
[0003] There are two main problems in the process of laser cladding WC reinforced composite coating: one is the decarburization and burning of WC; the other is the density of WC is 15.63g / cm 3 , far exceeding the density of the coating parent phase material, will sink to the bottom of the coating in the laser molten pool, resulting in uneven distribution of the coating structure, and the brittle WC ceramic reinforcement phase gathers near the interface to form stress concentration, which will induce coating crack formation. The above two problems greatly affect the performance of laser cladding WC reinforced composite coatings.
[0004] Therefore, it is necessary to control the decarburization and burning of WC and the uneven distribution of WC in the composite coating during the laser cladding process, and provide a new method for preparing high-performance WC reinforced composite coatings by laser cladding. Summary of the invention
[0005] Purpose of the invention: The purpose of the present invention is to provide a method for preparing a WC reinforced composite coating, so as to solve the problem of how to prepare a high-performance WC reinforced composite coating.
[0006] Technical solution: The method for preparing a WC reinforced composite coating according to the present invention comprises the following steps:
[0007] S1. Mixing ZrO2-WC composite powder and nickel-based alloy powder to obtain raw material powder; the ZrO2-WC composite powder has the same density as the nickel-based alloy powder, and the ZrO2-WC composite powder is a core-shell structure particle formed by ZrO2 coating WC particles;
[0008] S2. The raw material powder is clad on the surface of the metal substrate by laser cladding method to obtain a WC reinforced composite coating.
[0009] The present invention adopts ZrO2-WC composite powder as reinforcing phase, and the composite powder is mixed with parent phase powder in a certain proportion as cladding material for laser cladding to obtain a high-performance composite coating with no decarburization and burning of WC reinforcing phase, uniform distribution, and no cracks in the composite coating.
[0010] Preferably, in step S1, the particle size of the ZrO2-WC composite powder is 10-100 μm and the density is 8-9 g·cm -3 , where the volume ratio of ZrO2 to WC is 4-5:1.
[0011] The density of the ZrO2-WC composite powder is similar to that of the parent phase powder by adjusting the volume ratio of low-density ZrO2 and high-density WC in the composite powder.
[0012] Preferably, in step S1, the ZrO2-WC composite powder is prepared as follows:
[0013] (1) dissolving citric acid and polyvinyl pyrrolidone in ethylene glycol solution, then sequentially adding zirconium salt and WC particles, and fully stirring to obtain a mixed solution;
[0014] (2) stirring and heating the mixed solution, adding n-butylamine after reaching the reaction temperature, and reacting at a constant temperature to obtain a reactant;
[0015] (3) After cooling the reactants, centrifuging and collecting the precipitate, washing and drying to obtain a precursor product; and subjecting the precursor product to radio frequency plasma spheroidization to obtain a ZrO2-WC composite powder.
[0016] Preferably, in step (1), the zirconium salt comprises at least one of zirconium nitrate, zirconium chloride, zirconium sulfate, zirconium oxalate and zirconium carbonate, the mass ratio of zirconium salt to WC particles is 10-20:5-15, and the particle size of the WC particles is 1-3 μm.
[0017] Preferably, in step (1), the solid-liquid ratio of citric acid, polyvinyl pyrrolidone and ethylene glycol is 0.1-0.5 g:1.0-5.0 g:100-500 mL.
[0018] Preferably, in step (2), the stirring and heating condition is a stirring speed of 300-500 r·min -1 , heating rate is 3-5℃·min -1 The reaction temperature is 170-210° C., and the constant temperature reaction time is 3-5 hours; the volume ratio of n-butylamine to ethylene glycol is 5-25:100-500.
[0019] Preferably, in step (3), the parameters of the radio frequency plasma spheroidization are: plasma power of 38-42 kW, central gas flow rate of 15-25 L·min -1 , Ar flow rate in sheath gas is 40-60 L·min -1 , the H2 flow rate in the sheath gas is 20-28L·min -1 , carrier gas flow rate is 6-12L·min -1, powder feeding rate is 0.3-0.7g·min -1 , the system pressure is 12-18kPa.
[0020] Preferably, in step S1, the mass ratio of the ZrO2-WC composite powder to the nickel-based alloy powder is 1-3:2-4, and the nickel-based alloy powder includes at least one of Ni 625 powder, Ni 718 powder, Ni C-276 powder, Ni X-750 powder, and Ni 690 powder.
[0021] Preferably, in step S2, the laser cladding method is: using a coaxial powder feeding multi-pass overlapping cladding process, the laser power is 1700-1900W, and the laser scanning speed is 400-440mm·min -1 , powder feeding speed is 2.0-2.2r·min -1 The spot diameter is 3-5mm, the overlap rate is 45-55%, and inert gas is introduced during the cladding process. The inert gas can be argon, helium, nitrogen, etc.
[0022] Preferably, in step S2, the metal substrate is first polished to remove oxide scale before the cladding operation, and then the surface of the metal substrate is polished with sandpaper, and the oil and impurities on the surface of the metal substrate are cleaned with anhydrous ethanol and dried before use in the cladding operation.
[0023] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0024] The present invention adopts ZrO2-WC composite powder as a reinforcing phase and mixes it with a parent phase powder in a certain proportion as a cladding material for laser cladding. On the one hand, the protective effect of ZrO2 with a large heat of generation in the ZrO2-WC composite powder avoids decarburization and burning of WC during the laser cladding process. On the other hand, the volume ratio of low-density ZrO2 and high-density WC in the composite powder is adjusted to make the density of the composite powder close to that of the parent phase powder, effectively avoiding the large difference in density between the conventional WC reinforcing phase and the parent phase, which will sink to the bottom of the coating in the laser molten pool, thereby causing uneven tissue distribution, and the brittle WC ceramic reinforcing phase gathers near the interface to form stress concentration, which will induce the formation of coating cracks, thereby obtaining a high-performance composite coating with uniform distribution of reinforcing phase and crack-free composite coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the SEM morphology of the Ni625 powder used in the present invention;
[0026] Figure 2 The external SEM morphology of the ZrO2-WC composite powder used in Example 1;
[0027] Figure 3The internal SEM morphology of the ZrO2-WC composite powder used in Example 1;
[0028] Figure 4 XRD analysis results of laser cladding ZrO2-WC reinforced Ni625 composite coating in Example 1;
[0029] Figure 5 This is the low magnification SEM morphology of the laser cladding ZrO2-WC reinforced Ni625 composite coating in Example 1;
[0030] Figure 6 This is the high magnification SEM morphology of the laser cladding ZrO2-WC reinforced Ni625 composite coating in Example 1;
[0031] Figure 7 This is the SEM morphology of the laser cladding ZrO2+WC reinforced Ni625 composite coating in comparative example 1. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0033] Embodiment 1: A method for preparing a WC reinforced composite coating, comprising the following steps:
[0034] (1) 0.3 g of citric acid and 3.0 g of polyvinyl pyrrolidone were dissolved in 300 mL of ethylene glycol solution, and then 15 g of zirconium nitrate and 10 g of WC particles with a particle size of 1 to 3 μm were added in sequence and stirred for 45 min to obtain a mixed solution; the mixed solution was then transferred to a three-necked flask and the stirring speed of the heated magnetic stirrer was set to 400 r·min -1 , Heating rate 4℃·min -1 After the reaction temperature reaches 190°C, 15 mL of n-butylamine is added and the reaction is carried out at a constant temperature for 4 hours to obtain the reactant; the reactant is removed from the heating device and cooled, and the cooled reactant is centrifugally washed 4 times with anhydrous ethanol and dried in a vacuum drying oven at 90°C for 8 hours to obtain a precursor product; finally, a radio frequency plasma spheroidization device of model TekSphero-40 of Canadian TEKNA Company is used to treat the precursor product with the process shown in Table 1, and ZrO2-WC composite powder is obtained. The external SEM morphology of the ZrO2-WC composite powder is shown in Figure 2 As shown in Figure 1, the powder is also spherical, with a particle size of about 10 to 100 μm. The internal SEM morphology of the ZrO2-WC composite powder is as follows: Figure 3 As shown in the figure, the composite powder consists of many WC particles with a size of 1 to 3 μm and a ZrO2 protective layer coated on the surface of the WC particles. The ZrO2-WC composite powder within the size range required for laser cladding is screened. The volume ratio of low-density ZrO2 to high-density WC in the ZrO2-WC composite powder is between 4:1-5:1, and the density is 8-9 g·cm -3 .
[0035] Table 1 RF plasma spheroidization process parameters
[0036]
[0037]
[0038] (2) ZrO2-WC composite powder and Ni625 powder (Jiangsu Guoyi Special Alloy Co., Ltd.) were mechanically mixed at a mass ratio of 2.3 to obtain raw material powder; in this embodiment, the density of ZrO2-WC composite powder is the same as or similar to that of Ni625 powder. ZrO2-WC composite powder is a core-shell structure particle formed by ZrO2 coating WC particles; the SEM morphology of Ni625 powder is as follows Figure 1 As shown, the powder is spherical and has a particle size of about 20 to 60 μm.
[0039] (3) Using laser cladding method to clad the raw material powder on the surface of the metal substrate, specifically:
[0040] 316L stainless steel with a size of 100mm×100mm×10mm was used as the metal substrate, and raw material powder was used as the composite coating cladding material. Before cladding, the oxide scale on the surface of the metal substrate was removed with an angle grinder, then polished with sandpaper, and finally the surface oil and impurities were cleaned with anhydrous ethanol and blown dry. The cladding operation used the German LASERLINE LDF6000 fiber-coupled semiconductor laser and KAWASAKI robot to prepare the ZrO2-WC particle-reinforced Ni625 composite coating sample, and the coaxial powder feeding multi-pass overlapping cladding process was adopted. The laser power was 1800W and the laser scanning speed was 420mm·min -1 , powder feeding speed is 2.1r·min -1 The spot diameter is 4 mm, the overlap rate is 50%, and 20 L·min is introduced during the test. -1 Argon was used as the protective gas.
[0041] Figure 4 The XRD analysis results of the laser cladding ZrO2-WC reinforced Ni625 composite coating prepared in this embodiment show that the coating is mainly composed of γ-Ni solid, ZrO2 and WC. No W2C, M2C and WC other than WC are detected in the conventional laser cladding WC reinforced composite coating. 23 The C6 and other phases indicate that due to the protective effect of ZrO2 with high heat of formation, the WC of the ZrO2-WC composite powder is not decarburized and burned during the laser cladding process.
[0042] Figure 5 and Figure 6These are the low-magnification and high-magnification SEM morphologies of laser cladding ZrO2-WC reinforced Ni625 composite coatings, respectively. It can be seen from the figures that due to the similar density between the ZrO2-WC composite powder and the Ni625 parent phase powder, the conventional WC reinforcement phase will sink to the bottom of the coating in the laser molten pool due to the large difference in density between the parent phase, resulting in uneven tissue distribution. The brittle WC ceramic reinforcement phase gathers near the interface to form stress concentration, which will induce crack formation in the coating, and a high-performance WC reinforced composite coating with uniform distribution of reinforcement phase and crack-free composite coating is obtained.
[0043] Embodiment 2: The rest is the same as Embodiment 1, except that:
[0044] The zirconium nitrate was replaced by zirconium chloride; the mass ratio of zirconium chloride to WC particles was 10:5;
[0045] The material-liquid ratio of citric acid, polyvinyl pyrrolidone and ethylene glycol is 0.1 g·1.0 g·100 mL. The stirring and heating conditions are as follows: the stirring speed is 300 r·min -1 , heating rate is 3℃·min -1 , the reaction temperature is 170°C, the constant temperature reaction time is 3h; the amount of n-butylamine used is 5mL.
[0046] The parameters of RF plasma spheroidization are: plasma power of 38 kW and central gas flow rate of 15 L min -1 , the Ar flow rate in the sheath gas is 40 L·min -1 , the H2 flow rate in the sheath gas is 20 L·min -1 , carrier gas flow rate is 6L·min -1 , powder feeding rate is 0.3g·min -1 , the system pressure is 12kPa.
[0047] The Ni 625 powder is replaced by the Ni 690 powder, and the mass ratio of the ZrO2-WC composite powder to the Ni 690 powder is 1:2;
[0048] The laser power in the laser cladding operation is 1700W and the laser scanning speed is 400mm·min -1 , powder feeding speed is 2.0r·min -1 , the spot diameter is 3mm and the overlap rate is 45%.
[0049] Embodiment 3: The rest is the same as Embodiment 1, except that:
[0050] The zirconium nitrate was replaced by zirconium oxalate; the mass ratio of zirconium oxalate to WC particles was 20:15;
[0051] The material-liquid ratio of citric acid, polyvinyl pyrrolidone and ethylene glycol is 0.5 g·5.0 g·500 mL. The stirring and heating conditions are as follows: the stirring speed is 500 r·min -1 , heating rate is 5℃·min -1 , the reaction temperature is 210°C, the constant temperature reaction time is 5h; the amount of n-butylamine used is 25mL.
[0052] The parameters of RF plasma spheroidization are: plasma power of 42 kW and central gas flow rate of 25 L min -1 , Ar flow rate in sheath gas is 60 L·min -1 , the H2 flow rate in the sheath gas is 28L·min -1 , carrier gas flow rate is 12L·min -1 , powder feeding rate is 0.7g·min -1 , the system pressure is 18kPa.
[0053] The Ni 625 powder is replaced by the Ni 718 powder, and the mass ratio of the ZrO2-WC composite powder to the Ni 718 powder is 3:4;
[0054] The laser power in the laser cladding operation is 1900W and the laser scanning speed is 440mm·min -1 , powder feeding speed is 2.2r·min -1 , the spot diameter is 5mm and the overlap rate is 55%.
[0055] Embodiment 4: The rest is the same as Embodiment 1, except that:
[0056] Zirconium nitrate was replaced by zirconium sulfate; Ni 625 powder was replaced by Ni C-276 powder;
[0057] Comparative Example 1: The rest is the same as Example 1, except that:
[0058] 5.45 g of zirconium oxide with a particle size of 20-50 μm and 15 g of WC particles with a particle size of 1-3 μm were directly mixed and uniformly used as a control composite powder. The control composite powder was used to replace the ZrO2-WC composite powder to prepare a composite coating.
[0059] Comparative Example 2: The rest is the same as Example 1, except that:
[0060] The composite coating is prepared by replacing the ZrO2-WC composite powder with WC powder with a particle size of 1-3 μm.
[0061] XRD analysis of the composite coatings prepared in Examples 1-4 and Comparative Examples 1-2 revealed the presence of W2C, M 23C6 and other phases are used to determine whether WC has decarburization and burning during the laser cladding process. At the same time, the compressive strength of the coating is measured, and the results are as follows:
[0062] Table 2 Effect of different composite powders on WC decarburization and burning in coating
[0063]
[0064]
[0065] The results in Table 2 show that only the core-shell structure of ZrO2-WC composite powder can effectively avoid the decarburization and burning of WC during laser cladding, avoid cracks in the coating, and effectively improve the strength of the coating. In Comparative Example 1, after ZrO2 and WC were directly mixed, ZrO2 and WC could not form a composite, and both existed independently. ZrO2 could not solve the problem of WC decarburization, burning and sinking, such as Figure 7 As shown, the composite coating has cracks and its strength is significantly lower than that of Example 1.
Claims
1. A method for preparing a WC reinforced composite coating, characterized in that: The steps include: S1. Mixing ZrO2-WC composite powder and nickel-based alloy powder to obtain raw material powder; the ZrO2-WC composite powder and the nickel-based alloy powder have similar densities, and the ZrO2-WC composite powder is a core-shell structure particle formed by ZrO2 coating WC particles; S2. The raw material powder is clad on the surface of the metal substrate by laser cladding method to obtain a WC reinforced composite coating.
2. The method for preparing the WC reinforced composite coating according to claim 1, characterized in that: In step S1, the ZrO2-WC composite powder has a particle size of 10-100 μm and a density of 8-9 g·cm -3 , where the volume ratio of ZrO2 to WC is 4-5:
1.
3. The method for preparing the WC reinforced composite coating according to claim 1, characterized in that: In step S1, the ZrO2-WC composite powder is prepared as follows: (1) dissolving citric acid and polyvinyl pyrrolidone in ethylene glycol solution, then sequentially adding zirconium salt and WC particles, and fully stirring to obtain a mixed solution; (2) stirring and heating the mixed solution, adding n-butylamine after reaching the reaction temperature, and reacting at a constant temperature to obtain a reactant; (3) cooling the reactants, centrifuging and collecting the precipitate, washing and drying to obtain the precursor product; The precursor product is spheroidized by radio frequency plasma to obtain ZrO2-WC composite powder.
4. The method for preparing the WC reinforced composite coating according to claim 3, characterized in that: In step (1), the zirconium salt includes at least one of zirconium nitrate, zirconium chloride, zirconium sulfate, zirconium oxalate and zirconium carbonate, the mass ratio of zirconium salt to WC particles is 10-20:5-15, and the particle size of the WC particles is 1-3 μm.
5. The method for preparing the WC reinforced composite coating according to claim 3, characterized in that: In step (1), the solid-liquid ratio of citric acid, polyvinyl pyrrolidone and ethylene glycol is 0.1-0.5 g:1.0-5.0 g:100-500 mL.
6. The method for preparing the WC reinforced composite coating according to claim 3, characterized in that: In step (2), the stirring and heating conditions are as follows: the stirring speed is 300-500 r·min -1 , heating rate is 3-5℃·min -1 The reaction temperature is 170-210° C., and the constant temperature reaction time is 3-5 hours; the volume ratio of n-butylamine to ethylene glycol is 5-25:100-500.
7. The method for preparing the WC reinforced composite coating according to claim 3, characterized in that: In step (3), the parameters of RF plasma spheroidization are: plasma power of 38-42 kW, central gas flow rate of 15-25 L·min -1 , Ar flow rate in sheath gas is 40-60 L·min -1 , the H2 flow rate in the sheath gas is 20-28L·min -1 , carrier gas flow rate is 6-12L·min -1 , powder feeding rate is 0.3-0.7g·min -1 , the system pressure is 12-18kPa.
8. The method for preparing the WC reinforced composite coating according to claim 1, characterized in that: In step S1, the mass ratio of the ZrO2-WC composite powder to the nickel-based alloy powder is 1-3:2-4, and the nickel-based alloy powder includes at least one of Ni625 powder, Ni718 powder, Ni C-276 powder, Ni X-750 powder, and Ni 690 powder.
9. The method for preparing the WC reinforced composite coating according to claim 1, characterized in that: In step S2, the laser cladding method is: using a coaxial powder feeding multi-pass overlapping cladding process, the laser power is 1700-1900W, and the laser scanning speed is 400-440mm·min -1 , powder feeding speed is 2.0-2.2r·min -1 The spot diameter is 3-5mm, the overlap rate is 45-55%, and inert gas is introduced during the cladding process.
10. The method for preparing the WC reinforced composite coating according to claim 1, characterized in that: In step S2, the metal substrate is first polished to remove the oxide scale before the cladding operation, and then the surface of the metal substrate is polished with sandpaper, and the oil and impurities on the surface of the metal substrate are cleaned with anhydrous ethanol and dried before use in the cladding operation.
Citation Information
Patent Citations
Laser cladding method for strengthening surface of piercing point
CN101519778A
Process for coating silicon oxide and zirconium oxide composite film on surface of tungsten carbide nanopowder
CN103601503A
Method for coating zirconia on surface of tungsten carbide-cobalt composite powder
CN108889941A
Method for preparing WC-co powder used for thermal spraying
WO2015169132A1
Cited By
In-situ multi-shell TiWC2 ceramic reinforced iron-based laser cladding coating and preparation method thereof
CN122466449A